Antifungal soybean protein concentrate adhesive as binder of rice husk particleboards - Larregle, Andrés (2021)
The aim of this research was to prepare an antifungal soybean protein concentrate (SPC) adhesive containing carvacrol (CRV) as a bioactive agent able to delay the attack of molds and yeast during storage of SPC adhesive at 4◦C as water-based systems. CRV was incorporated in SPC slurry at 0.5% v/v (~10 times its minimum inhibitory concentration against Aspergillus terreus, used as model fungus), to ensure its long-term action. CRV scarcely altered the thermal properties, structure and apparent viscosity of SPC adhesive. Active SPC aqueous dispersion was microbiologically stable for at least 30 days at 4◦C where the colonization begins, while control SPC was visually colonized from the second day. Rice husk (RH) particleboards of density ~900 kg/m3 were manufactured using the active SPC stored for 0, 10, 20, and 30 days as a binder. Modulus of elasticity, modulus of rupture and internal bond of RH–control SPC (without CRV) panels were 12.3 MPa, 2.65 GPa and 0.27 MPa, respectively, and were statistically unaltered compared with those obtained with fresh SPC, regardless of the presence of CRV or the storage time. This last implies that active SPC should not necessarily have to be prepared daily and/or be used immediately after its preparation. Since it is microbiologically stabilized, it can be store at least for 30 days, ensuring the stability of the protein. The quality of the adhesive was evidenced by the consistent properties of the adhesive, expanding its potential use and commercialization.